Society’s Perception on Residences in Development Area Attachment: A Case Study of PLPBK in Tulusrejo Village, Lowokwaru Sub-District, Malang City - Sitaresmi, Devi Triwidya; Dwi Ari, Ismu Rini; Wijaya, I Nyoman Suluh (International Journal of Social Sciences and Management, 2018)
This study involved residents of RT 02 and RT 03, Tulusrejo sub-district. The setting of this study was one of the government’s target residence related to the project of Community-Based City and Residence Planning or Penataan Lingkungan Pemukiman Berbasis Komunitas (PLPBK), which success depended on society’s participation. Social bonds that result from long-term social interaction and life journey create emotional feeling upon their residences (Hummon, 1990). The place where people live and do their daily activities has certain deep meaning for them (Kyle et al, 2004), which at the same time affects the social psychological domain called place attachment (Lewicka, 2011). Thus, it was necessary to create strong social bonds and strengthen residents’ place attachment feeling for the success of the PLPBK program. In this study, social network mapping was analyzed using the Social Network Analysis (SNA). Meanwhile, to explain residents’ perception on their residence, Multidimensional Scaling was used. The result of this study exhibits that some social groups were formed upon certain similarities and membership of a certain organization. Besides, social groups were also formed by similar community attachment. Int. J. Soc. Sc. Manage. Vol. 5, Issue-1: 46-50